Moral Injury and the Implicit or Explicit Language of Sexual Violence during Warfare in Fifteenth-Century Flemish Chronicles - Demets, Lisa (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2025)
In late medieval Flemish chronicles, sexual violence is frequently depicted as a consequence of war. Chroniclers distinguished between rape as a crime of passion and rape by armed coercion, reflecting broader societal perceptions of sexual violence. These accounts often served to demonize enemies, portraying them as morally corrupt, but they also reveal anxieties about leadership failures and moral transgressions within one’s own ranks that led to plundering, harassment, and ravishment. Both Burgundian and urban chroniclers engaged with this discourse: some highlighted ducal anti-rape policies to reinforce Burgundian legitimacy, while others exposed the contradictions between official prohibitions and the realities of war. Additionally, the portrayal of sexual violence intersects with the concept of moral injury, as chroniclers—both explicitly and implicitly—documented the violation of deeply held ideals about just warfare. As such, chroniclers constructed selective memories of sexual violence during warfare and revolts.